Maternity leave and exclusive breastfeeding - Karina Abibi Rimes; Maria Inês Couto de Oliveira; Cristiano Siqueira Boccolini (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To analyze the association between maternity leave and exclusive breastfeeding and to estimate the prevalence of exclusive breastfeeding in children under six months of life. METHODS: Cross-sectional study, with mothers of children under six months of life, attended in primary health care units with Breast Milk Collection Services in the municipality of Rio de Janeiro, Brazil, in 2013 (n = 429). We analyzed characteristics concerning: maternal sociodemographic aspects, household, prenatal care, childbirth, maternal lifestyle, the child, health care, and infant feeding. Adjusted prevalence ratios (APR) were obtained by Poisson regression with robust variance according to hierarchical approach, and we kept in the final model variables that were associated (p ≤ 0.05) with exclusive breastfeeding (outcome). RESULTS: Among the interviewed mothers, 23.1% were on maternity leave and 17.2% were working. The prevalence of exclusive breastfeeding was 50.1%. The maternal work with maternity leave was associated with higher prevalence of the outcome (APR = 1.91; 95%CI 1.32-2.78), compared with mothers who worked without maternity leave. CONCLUSIONS: Maternity leave has contributed to the practice of exclusive breastfeeding for children under six months of life, which indicates the importance of this benefit in protecting exclusive breastfeeding for women inserted in the formal labor market.